Investigating health factors as predictor of early drop-out of first year accounting students at the University of the Free State, South Africa - Beyers, Christa; Joubert, Hanli (Afrika Focus, 2016)
Introduction: The future of the South African workforce looks bleak given the challenges posed, not only by health factors, including HIV and AIDS, but also the success and throughput rate of rst year university students. Methodology: The research in this study was conducted in 2013 using a post-positivist approach and applying an interpretive stance using a mixed method approach, which included a quantita- tive non-experimental predictive multivariate design as well as focus group interviews to triangu- late the ndings. Results: We present ndings that psychosocial background factors, physical health and emotion- al health in uence success and non-completion rates among rst year students at the University of the Free State, South Africa. Conclusion: We argue that early identi cation of poor psychosocial background, including health factors, can assist in empowering youths helping them to make healthy decisions and deal with stressful situations in a way that will not compromise their academic success.